A Survey on Big Data in the Media and Entertainment Industry - Annisaa Nurhayati (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2019)
Big Data has affected all industries, including the media dan entertainment industries. The popularity of using mobile devices and the internet has changed the way people enjoy entertainment. This popularity also generates data streams from many sources with various data formats and large volumes, known as big data. Carrying out big data analysis can help the media industry and entertainment achieve its goals, like providing content that makes users happy, provides user experience, and increases profits. Many researchers have conducted research on the use of big data in the media and entertainment industries. The purpose of this paper is to provide an overview of the problems, challenges and various technologies related to Big Data in the media and entertainment industries.